Good practices in watershed management: lessons learned in the mid hills of Nepal (Kathmandu, 2007)
This publication documents the experience and lessons learned from the PARDYP-Nepal sites. Detailed hydro-meteorological data, together with land use related data, were collected and analysed to increase understanding of topics such as land degradation and water management. The results have been archived for future research use on climate change, land use dynamics, and sustainable mountain agriculture and are partly presented here. Many of the easy-to-implement technological options for improved livelihoods and community-based management of natural resources developed by the project are relevant across the middle altitude zones of the Himalayan region and are also presented here. The document also addresses many of the questions commonly asked about managing mountain natural resources and forms the basis for developing the next generation of watershed management programmes.
Keywords: Watershed management-Nepal